Dual Roles of Coconut Oil and Its Major Component Lauric Acid on Redox Nexus: Focus on Cytoprotection and Cancer Cell Death - Ramya, Venkatesan; Shyam, Karuppiah Prakash; Kowsalya, Eshwaran; Balavigneswaran, Chelladurai Karthikeyan; Kadalmani, Balamuthu (Frontiers in Neuroscience, 2022)
It has been reported that coconut oil supplementation can reduce neuroinflammation. However, coconut oils are available as virgin coconut oil (VCO), crude coconut oil (ECO), and refined coconut oil (RCO). The impact of coconut oil extraction process (and its major fatty acid component lauric acid) at cellular antioxidant level, redox homeostasis and inflammation in neural cells is hitherto unexplained. Herein, we have shown the antioxidant levels and cellular effect of coconut oil extracted by various processes in human neuroblastoma cells (SH-SY5Y) cultured in vitro. Results indicate VCO and ECO treated cells displayed better mitochondrial health when compared to RCO. Similar trend was observed for the release of reactive oxygen species (ROS), key oxidative stress response genes (GCLC, HO-1, and Nqo1) and inflammatory genes (IL6, TNFα, and iNOS) in SH-SY5Y cells. Our results signified that both VCO and ECO offer better neural health primarily by maintaining the cellular redox balance. Further, RCO prepared by solvent extraction and chemical refining process lacks appreciable beneficial effect. Then, we extended our study to find out the reasons behind maintaining the cellular redox balance in neuroblastoma cells by VCO and ECO. Our GC-MS results showed that lauric acid (C14:0) (LA) content was the major difference in the fatty acid composition extracted by various processes. Therefore, we evaluated the efficacy of LA in SH-SY5Y cells. The LA showed dose-dependent effect. At IC50 concentration (11.8 µM), LA down regulated the oxidative stress response genes and inflammatory genes. The results clearly indicate that the LA inhibited the neuroinflamation and provided an efficient cellular antioxidant activity, which protects the cells. The efficiency was also evaluated in normal cell line such as fibroblasts (L929) to cross-validate that the results were not false positive. Different concentration of LA on L929 cells showed high compatibility. From our observation, we conclude that VCO and ECO offers better cellular protection owing to their powerful antioxidant system. Therefore, we advocate the inclusion of either VCO and/or ECO in the diet for a healthy lifestyle.